Analisis Kesalahan Siswa SMP dalam Menyelesaikan Soal Bangun Ruang - Ratih Ayu Utami (MATHEdunesa, 2020)
This study aims to: (1) describe the location of the students' mistakes in solving geometrical problems, (2) to describe the students' mistakes in solving geometrical problems, and (3) to describe the factors that cause students' errors in solving geometric problems. This research is a qualitative study using test and interview methods and was conducted at SMP Negeri 21 Surabaya. Selection of subjects based on criteria, namely students who made many mistakes on indicators of the location and type of error, variation of errors, openness and fluency of the subject to communicate during the interview process.